Strengthening Affective Commitment through Social Support: The Experience of Women Leaders in a Diaspora Organization - Fitriana, Nita; Inah (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Objective – This study examines the affective commitment of women leaders in Fatayat NU Malaysia by exploring its meaning, identifying the sources and forms of social support they receive, and explaining how such support shapes and sustains commitment in a volunteer-based socio-religious organization in a diaspora context. Design/methodology/approach – A qualitative case study design was employed within a constructivist-interpretivist paradigm. Data were collected through semi-structured in-depth interviews with six women leaders who had served or were serving as chair or vice chair of Fatayat NU Malaysia during the 2016–2025 leadership periods. Observation and organizational documents complemented the interviews, and the data were analyzed using Braun and Clarke’s Reflexive Thematic Analysis. Findings – Affective commitment among women leaders extends beyond emotional attachment to include spiritual meaning, self-development, and a sustainability-oriented commitment. Fatayat is perceived as a second home, a learning space, and a field of khidmah (service). Social support is multi-layered, encompassing family, internal organizational administrators, and friends. This support reduces stress and role conflict, enhances feelings of competence, security, and comfort, and strengthens emotional attachment, belonging, and organizational meaning. Research limitations/implications – The study extends the literature by showing that affective commitment in women-led volunteer-based socio-religious organizations is emotional, spiritual, and reflective, while social support operates as a multi-layered relational ecosystem. Practical implications – Organizations need more responsive support systems through stronger family involvement, teamwork, delegation, emotional support spaces, and cadre development strategies for diaspora women leaders. Originality/value – The study contributes by focusing on women leaders in a diaspora-based socio-religious volunteer organization and by explaining the relational mechanisms linking multi-layered social support and affective commitment.